P-42 An innovative approach to transform end of life care in a prison setting. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Hart, Derek; Thomas, Martin; Lawley, Liz
Abstract : Since the End of Life Care Strategy (Department of Health, 2008) stated that high quality services should be available in all locations, including prisons, there has been recognition of the increasing demand for end of life care within UK prisons as their population ages, presenting both practical and emotional care challenges (Turner, 2018). Inequities in palliative care provision for prisoners as opposed to the general population have been highlighted (Fletcher, Payne, Waterman et al ., 2013; Prisons and Probation Ombudsman, 2017). Despite hospice clinical nurse specialist (CNS) involvement in providing end of life care within the local category C prison, joint working between the hospice CNS and the prison matron identified the need to improve access to and choice in end of life care. Referral rates for palliative care support were low and restricted to those with cancer, minimal advance care planning (ACP) and support was in place and prisoners were being transferred to another prison with palliative care beds for last days of life care. Burdett funding was obtained for a one-year project to address this. Through a process of consultation and dialogue with prison management and healthcare staff, specific changes were made to end of life care provision within the prison including an end of life education programme for prison staff, monthly multi-disciplinary meetings to identify those at end of life, introduction of in-reach clinics and cell visits and improved access to out-of-hours teams, end of life services and as needed medication for symptom control. In the year following completion of the project, referrals to the palliative care team doubled and included non-malignant conditions such as end stage respiratory disease. Prison staff reported more compassionate and positive attitudes and understanding of end of life care issues amongst staff and inmates, with ACP and identification of preferred place of care becoming embedded within the culture of the prison. This has allowed individuals to receive last days of life care within the prison.